Late Wisconsinan Cordilleran and Laurentide Glaciation of the Peace River Valley East of the Rocky Mountains, British Columbia - Hartman, Gregory M.D.; Clague, John J.; Barendregt, René W.; Reyes, Alberto V. (NRC Research Press (a division of Canadian Science Publishing), 2018)
In the past, researchers have disagreed over the maximum extent of the Cordilleran Ice Sheet in the Peace River valley during the Late Wisconsinan. Some workers argued that Cordilleran ice reached beyond the Rocky Mountains and briefly coalesced with the Laurentide Ice Sheet on the westernmost Interior Plains. In contrast, others asserted that Cordilleran ice did not reach beyond the eastern front of the Rocky Mountains. Stratigraphic interpretation of three sections within a Middle Wisconsinan paleovalley and re-examination of a previously published regional stratigraphic framework show that western-sourced ice (likely the Cordilleran Ice Sheet) extended east of the mountain front during the Late Wisconsinan, prior to the incursion of the Laurentide Ice Sheet into the area. This conclusion has implications for Cordilleran Ice Sheet reconstruction and modelling, and provides insight into the interactions between the Cordilleran and Laurentide ice sheets during the last glaciation. The accepted manuscript in pdf format is listed with the files at the bottom of this page. The presentation of the authors' names and (or) special characters in the title of the manuscript may differ slightly between what is listed on this page and what is listed in the pdf file of the accepted manuscript; that in the pdf file of the accepted manuscript is what was submitted by the author.